2009
DOI: 10.1007/s11244-009-9409-8
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Zeolite Catalyst for CO2 Reforming of Methane

Abstract: The catalytic activity of Ni-Rh on the synthesized BEA zeolite in carbon dioxide reforming of methane has been investigated. Catalysts were prepared using the incipient wetness impregnation method, with a total content of metals up to 5 wt%. Catalysts were characterized through XRD, TPR, N 2 adsorption, SEM, AAS, TG/DSC analyses. The prepared Ni-Rh zeolites were tested for their catalytic activity at 700°C, at atmospheric pressure, and at CH 4 /CO 2 ratio of 1. Catalytic results showed that bimetallic based ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Recently, the activity of different zeolite-supported Ni catalysts for methane reforming with carbon dioxide has been investigated [10,11]. Among these, MFI-and USY-type zeolites greatly improve both the activity and the selectivity of the reaction because of their suitable properties as supports for catalysts in reforming reactions, such as their microporous structure, high surface area and high affinity for CO 2 adsorption [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the activity of different zeolite-supported Ni catalysts for methane reforming with carbon dioxide has been investigated [10,11]. Among these, MFI-and USY-type zeolites greatly improve both the activity and the selectivity of the reaction because of their suitable properties as supports for catalysts in reforming reactions, such as their microporous structure, high surface area and high affinity for CO 2 adsorption [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the pore of molecular sieve SBA-15 is normally positive charged, but by using plasma treatment the pores can be made negative. [55,56,82] In 1996, Chang et al [119] reported high activity for a ZSM-5 supported Ni catalyst with high coke resistance for CO 2 reforming. [115] This will lead to a convenient preparation of molecular sieve supported Ni catalysts for CO 2 reforming.…”
Section: Preparation Methods Effectsmentioning
confidence: 99%
“…Nowosielska et al [54] compared Al 2 O 3 and SiO 2 -supported Ni and Ni-Rh catalysts. The recent work on molecular-sieve-supported Ni-Rh catalysts [55,56] suggested again that the support has a significant effect. They confirmed the support effect reported by Wang and Ruckenstein.…”
Section: Promotersmentioning
confidence: 99%
See 2 more Smart Citations